PERENCANAAN MANAJEMEN KONSTRUKSI PEMBANGUNAN GEDUNG AULA ASRAMA HAJI PONTIANAK: PERENCANAAN MANAJEMEN KONSTRUKSI PEMBANGUNAN GEDUNG AULA ASRAMA HAJI PONTIANAK - Septiadi, Eki Hermi; Arif, robby Mauludy (RETENSI, 2021)
In project implementation, it is necessary to have a construction management plan so that projectimplementation can be well planned and in accordance with the Indonesian Standard (SNI). Therefore, it isnecessary to plan construction management on the construction of the Pontianak Hajj Dormitory Hall,especially on building structure work which aims to get a more efficient and effective final result for Cost,Duration Time, Human Resources (HR), Quality, Occupational Health Safety (K3 ) where these aspects areinterconnected in construction management planning.Sources of data used in this study are secondary data and primary data included in the qualitativemethod. Based on the processed data, the final results include the Implementation Budget Plan (RAP), TimeSchedule, Network Planning (NWP), Manpower Needs, Quality Control Tables, Identifying Hazards, RiskAssessment, Personal Protective Equipment (PPE), and Work Safety Equipment ( APK), which will be used as areference in the implementation of development. The results of the Calculation of the Implementation Budget Plan (RAP) for the construction of thePontianak Hajj Dormitory Hall is Rp. 5,177,381,673.21 (“Five Billion One Hundred Seventy Seven MillionThree Hundred Eighty One Thousand Six Hundred Seventy Three Rupiah”), as well as the calculation result oftime requirement or duration for development planning is 13 weeks or 86 calendar days. There must be goodcooperation for all parties involved because the success of a project is largely determined by careful planningand good management.